Humanising Punishment?: mitigation and "Case-Cleansing" Prior to Sentencing - Tata, Cyrus (Oñati Socio-Legal Series, 2019)
The purpose of this article is to stimulate new thinking about the role of the humanisation of the person to be sentenced. By rendering the person’s offending more comprehensible, humanisation is assumed to obstruct harsh penal treatment and mechanical case-disposal. Distinctively, however, this article argues that "humanisation work" also achieves profound latent effects. By resolving the potential threat of a person’s own account appearing to be at odds with her formal admission of guilt (e.g. guilty plea), humanisation work enables efficient case-disposal. Applying Douglas’ work on purity and pollution, and with empirical illustrations, I show how the "dirty work" of humanising the person to be sentenced cleanses cases of troubling ambiguities, making punishment easier to impose with confidence. Nevertheless, humanisation work can, especially if the communicative distance between sentencer and the person sentenced is reduced, also be a facilitator of inclusive and empathic penal sentiments.